Evaluation Of Palm Oil Potentiality As A Liquid Dielectric Fluid In High Voltage Applications - Abdullahi, Usman Umar (2004)
Electrical insulating and dielectrical materials can be broadly divided into; gaseous, liquids, vacuum and solids. These materials are widely used in electrical components like, circuit breakers, transformers, cables and capacitors. Liquids dielectrics in particular are preferred because of their ability to have self-cure to situations leading to partial or total discharges. Petroleum and mineral based fluids have, for almost half a centuary, been used for cooling and insulation purposes. Their popularity stems out of their availability and cheapness. However recent evidence has shown deficiencies with these fluids. They have low properties especially flash and fire points and most importantly low dielectric break down voltage. The most serious of these shortcomings is the inability to meet up with health and environmental laws. This is because they are not organic and hence not biodegradable; their spillage takes very long time to decompose. These developments have led to seeking alternatives in vegetable based fluids. The fluids that have been tested and to be used as dielectric fluids include Castor oil, Coconut oil, Soya bean oil, and Rapeseed oil. The present work has measured the properties of palm oil against the IEEE C637 and ASTM D section for possible use as a dielectric fluid. The results show that refined palm oil has break down voltage of 75 KV/mm, flash point (>220), fire point (>220) and moisture content (0.08%). Hence these have shown the potential of palm oil as a dielectric fluid. However future work should focus on further investigation before field application. Malaysia as country stands a lot of gains in this type of research, since it is the world leader in the palm oil production.